Research on the impact of managerial capabilities on the digital transformation of enterprises - Fu, Jialin; Zhang, Nana; Li, Fei (Journal of Business Economics and Management, 2023)
Digitalization has brought profound changes to enterprises. As the main decision maker of firm, manager has an important impact on the digital transformation of enterprises that cannot be ignored. Based on the perspective of managerial heterogeneity, we tested the impact of managerial ability on the digital transformation of enterprises in China context. The results showed that managerial ability has a significant positive impact on the digital transformation of enterprises, that is, the stronger the managerial ability, the higher digitalization of firm. The mechanism study confirmed that managerial ability can overcome strategic inertia and improve capital allocation efficiency, then promote digital transformation of firm. Further research showed that the younger the top management team, the more significant the positive effect is; Independent directors can provide resources and play a consulting role to promote the impact of managerial ability on the digital transformation of firm; The older the firm is, the stronger the organizational inertia is, which can impede the impact of managerial ability on the digital transformation of firm. This study enriches the literature about executives, and has a certain practical significance for digitalization implement of enterprises.